“A Sombra Da Gameleira”: Literatura Contemporânea E Os Rumos Da Produção Feminina Na Paraíba - Campos Júnior, José de Sousa (2015)
Although it still needs dissemination and exploitation, female literature is reaching areas in academic discussion not achieved in decades ago. The democratization and expansion of the literary market are essential for such works to reach a growing audience, causing writers of places away from large urban centers to also have a chance of publication. Thus, the main objective of this paper is to discuss the historiographical and literary assumptions that put women's production in a secondary place in relation to male production, especially in the state of Paraíba. As specific objectives, we will: reflect on the space occupied by the female production in the local literary historiography; analyze the theoretical assumptions of the main history books of Brazilian literature, questioning them and proposing new forms of organization of literary history; discuss about the nature of literature in order to reach a conceptualization of work and literary historiography adopted in this research; the construction of a book of the writers of Paraíba from the data collected in this research implementation period, organizing, for that construction, a concept of female Paraiba writer; and point out the trends of female authors of literature in Paraíba.